BRASÍLIA IMAGINED: the city represented through its symbolic processes - Fávaro Garrossini, Daniela; dos Santos, Fátima Aparecida; Melo Franco Nery, Beatriz (DAT Journal, 2020)
It is intended in the present study, stemming from the methodology created by Armando Silva (2006) for the symbolic composition of “Cities Imagined”, to investigate the similarities and differences between the city portrayed in media and the city as it is lived and perceived by its residents. The research is focused on urban space from the citizen’s perspective, where the imaginary is imposed, at first, as a set of images and signs, of thought objects and everyday life, whose reach and coherence may vary and whose limits do not cease to be redefined. We begin from this point of view for understanding it is essential to think about the logics of communication, city and citizenship using parameters other than the distributive and efficient paradigm or traditional approaches, and so define an agenda and lines of research development and social intervention based on the language of its citizens and the demand for the common.